Depositional Cycles of Muara Wahau Coals, Kutai Basin, East Kalimantan - Anggayana, Komang; Rahmad, Basuki; Widayat, Agus Haris (Indonesian Journal on Geoscience, 2014)
http://dx.doi.org/10.17014/ijog.v1i2.183Fifteen samples were taken ply by ply from a 33 m thick drill core of Muara Wahau coal seams for interpretation of depositional environments. Generally, lithotype variation in the bottom part of the coal seams has a lower frequency than in the upper part. Petrographical analysis was performed to determine the maceral composition, groundwater index (GWI), and gelification index (GI). The samples from lower sections show much higher GWI-GI values and lower variation frequency than from the upper section. This characteristic is interpreted as the result of development of mesotrophic to ombrotrophic peats during the deposition of lower to upper parts of the section, respectively. During the development of the mesotrophic peat, water was more abundant and relatively stable in budget. However, during the development of ombrotrophic peat, water was less abundant and relatively not stable in budget. The latter is related to the water supply depending only on rain, resulted in the more sensitive water table in the om- brotrophic peat. The unstable water table is thought as the reason of higher variation frequency of lithotype, GWI, GI, as well as maceral composition in the upper part of the core. Unstable water table would lead to moist condition in the uppermost layer of the ombrotrophic peat, favoring fungi to grow. This is confirmed by the higher abundance of sclerotinite maceral in samples from the upper part of the coal core.